2012
DOI: 10.1080/10550887.2011.642754
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Gambling Severity in a Community Sample of Gamblers

Abstract: Although sleep has been extensively studied in substance related disorders, it has yet to be examined as thoroughly in gambling-related disorders. The purpose of this study is to examine the relationship between gambling severity and sleep disturbances in a sample of non-treatment seeking gamblers (N = 96) using the Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS). Mean ESS scores for recreational, problem, and pathological gamblers were 4.13, 5.81, and 8.69, respectively, with a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 91 publications
4
20
0
2
Order By: Relevance
“…By controlling for a broad spectrum of psychiatric illnesses, this study suggests the sleep complaints seen in gamblers are not an effect of diagnosable psychiatric disorders. While previous studies have demonstrated that gamblers often experience sleep complaints during crisis or withdrawal (Lesieur and Custer 1984; Lesieur and Rosenthal 1991; Rosenthal and Lesieur 1992), these findings support the notion that individuals with gambling pathology are more prone to sleep disturbances (Parhami et al 2012). …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…By controlling for a broad spectrum of psychiatric illnesses, this study suggests the sleep complaints seen in gamblers are not an effect of diagnosable psychiatric disorders. While previous studies have demonstrated that gamblers often experience sleep complaints during crisis or withdrawal (Lesieur and Custer 1984; Lesieur and Rosenthal 1991; Rosenthal and Lesieur 1992), these findings support the notion that individuals with gambling pathology are more prone to sleep disturbances (Parhami et al 2012). …”
Section: Discussionsupporting
confidence: 59%
“…Notably, in a recent sample of current community gamblers, Parhami and colleagues (2012) found a stepwise decrease in sleep quality among recreational, problem, and pathological gamblers, and they found significantly elevated daytime sleepiness in pathological gamblers compared to recreational gamblers. While this was the first study to use objective sleep measures in the gambling population, the sample size ( n = 96) was inadequate to statistically control for confounding variables, notably comorbid psychiatric conditions.…”
Section: Introductionmentioning
confidence: 97%
“…This outcome can be explained by the smaller number of gamblers in the red group. Use of computers at night is not only associated with symptoms found in gambling disorder (sleep disturbances, perceived stress, symptoms of depression, and reduced performance) [51,52,53] but also with the gambling disorder itself [54,55]. Likewise, there are concerns regarding gambling in the workplace [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that there are many studies documenting sleep disturbances in cancer (Sharma et al, 2012), and several studies showing the benefits of treating sleep disorders in the context of cancer (Garland et al, 2011, 2014; Roscoe et al, 2007; Sharma et al, 2012). Also, sleep disturbances have been described in other chronic diseases as well, such as pain syndromes (Besteiro Gonzalez et al, 2011; Landis, 2011; Lindstrom et al, 2012; Perlis et al, 1997; Wagner et al, 2012), dementias (Jaussent et al, 2012; Jirong et al, 2013; Zhou et al, 2012), human immunodeficiency virus (HIV) (Gamaldo et al, 2013b; Saberi et al, 2013; Taibi, 2013), and others (Cengic et al, 2012; Chakravorty et al, 2013; Jensen et al, 2013; Parhami et al, 2012; Wallhausser-Franke et al, 2013). This review focuses primarily on cardiometabolic disease, since the goal is to understand the potential role of sleep disturbance in preventing chronic disease.…”
Section: What Is Meant By ‘Cardiometabolic Disease?’mentioning
confidence: 99%